2020
DOI: 10.3892/ol.2020.11584
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between preoperatively predicted and postoperatively observed renal function using an imaging‑based approach: A retrospective cohort study

Abstract: The aim of the present study was to preoperatively predict renal function following partial nephrectomy (PN) using an imaging-based approach and to examine the correlation between preoperatively predicted and postoperatively observed renal function in the study cohort. A total of 128 consecutive patients who underwent PN between May 2015 and March 2018 and had available clinical data were included in this study. A hand-scripting method was used to estimate the defected volume (Vdef) from preoperative computeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…e possible reason is that the larger the diameter of the renal tumor, the less the nephrons can be retained after the complete resection of the renal tumor, and the larger the diameter of the tumor also increases the difficulty of the operation, resulting in prolonged resection and suture time and WIT, which in turn leads to poor renal function after the operation [16]. Patients with low GFR before operation can cause a series of biochemical changes such as decreased renal blood flow, damaged renal blood vessels, and decreased glomerular ultrafiltration coefficient after undergoing renal artery occlusion and tumor resection during RLNSS operation, resulting in decreased ATP, increased oxygen free radicals, calcium overload, and apoptosis in patients' bodies, further leading to pathological changes in the renal parenchyma structure, which will aggravate renal function damage after operation [17]. erefore, aiming at the patients with low GFR value before operation, the medical staff should make good preparations before operation and take measures to protect the renal function during operation and try their best to reduce the damage of renal function after operation by selecting drugs with less renal toxicity during the perioperative period, actively regulating blood pressure and blood sugar, dropping inosine before renal artery occlusion, and shortening WIT.…”
Section: Discussionmentioning
confidence: 99%
“…e possible reason is that the larger the diameter of the renal tumor, the less the nephrons can be retained after the complete resection of the renal tumor, and the larger the diameter of the tumor also increases the difficulty of the operation, resulting in prolonged resection and suture time and WIT, which in turn leads to poor renal function after the operation [16]. Patients with low GFR before operation can cause a series of biochemical changes such as decreased renal blood flow, damaged renal blood vessels, and decreased glomerular ultrafiltration coefficient after undergoing renal artery occlusion and tumor resection during RLNSS operation, resulting in decreased ATP, increased oxygen free radicals, calcium overload, and apoptosis in patients' bodies, further leading to pathological changes in the renal parenchyma structure, which will aggravate renal function damage after operation [17]. erefore, aiming at the patients with low GFR value before operation, the medical staff should make good preparations before operation and take measures to protect the renal function during operation and try their best to reduce the damage of renal function after operation by selecting drugs with less renal toxicity during the perioperative period, actively regulating blood pressure and blood sugar, dropping inosine before renal artery occlusion, and shortening WIT.…”
Section: Discussionmentioning
confidence: 99%
“…In these types of operations, the volume of functional renal parenchyma that is removed is much lesser compared to partial nephrectomy procedures. This statement is supported by relevant volumetric analysis studies on the effect of FRPV change on renal function decrement in patients undergoing PN (45,46). Consequently, by neglecting the term of the absolute change in creatinine levels in Expression 15.4, the linear Equation 16.2 is finally obtained.…”
Section: Methodsmentioning
confidence: 70%
“…In fact, the correlation coefficient between the proportion of preserved FRPV and eGFR was estimated ranging from 83% to 96%, highlighting a clearly linear relationship. Finally, in another study of similar interest, Liu et al aimed to preoperatively predict the level of renal function in patients submitted to partial nephrectomy by developing an image-based volumetric analysis model (46). In their model the researchers utilized three basic equations, while they also included the volume of the contralateral healthy kidney in their volumetric calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Research has proven that radical nephrectomy gradually restores renal function in patients [ 2 , 13 ]. Figures 1 and 2 show that the renal function of most patients decreased after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, radical nephrectomy is one of the options for treating malignant renal tumours [ 1 ]. Removal of the kidney inevitably reduces the functional renal parenchyma, resulting in loss of renal function [ 2 ]. Previous studies have demonstrated that older age, high comorbidity rates, and low preoperative estimated glomerular filtration rate (eGFR) are associated with chronic kidney disease (CKD) after radical nephrectomy [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%